Enhanced Activity and Stability of a Carbon‐Coated Alumina‐Supported Pd Catalyst in the Dehydrogenation of a Liquid Organic Hydrogen Carrier, Perhydro 2‐(n‐methylbenzyl)Pyridine. Issue 17 (20th July 2018) - Oh, Jinho; Kim, Tae Wan; Jeong, Kwanyong; Park, Ji Hoon; Suh, Young‐Woong
Abstract: The activity and stability of supported Pd catalysts are of crucial importance in the dehydrogenation of perhydro 2‐( n ‐methylbenzyl)pyridine (H12 ‐MBP) reported as a potential liquid organic hydrogen carrier. Because of good stability examined in many hydroprocessing reactions, carbon‐coated alumina (CCA) was chosen as a support for Pd loading and prepared by the pyrolysis of glycerol solution with different concentrations. The catalytic activity and stability of Pd/CCA catalysts exhibited a volcano‐shaped relationship with the carbon content. Various characterization results revealed that the degree of carbon coating affected the acidity, Pd loading and particle size, reactant adsorption capacity, and H2 release at low temperatures. At an optimal carbon content (3.3 wt % in this work), these properties are believed to be balanced well, thus showing the best catalytic performance. Moreover, the improvement of catalytic activity was examined with supported Pd on carbon‐coated silica‐alumina of 3.3 wt % carbon content. Abstract : Surface heterogeneity matters : The homogeneous alumina surface is heterogenized by carbon coating formed at acid sites, dominantly strong acid sites. However, if the coating is excessive, Al2 O3 surface goes back to the homogeneous carbon surface. Due to such a surface change, carbon‐coated Al2 O3 supported Pd catalysts in the dehydrogenation exhibited the volcano‐shaped activity and stability trends as a function of carbon coating.